Monitoring and controlling the electricity usage of 2 Room rented house based on IoT - Dewi, Citra; Rizki Pratama, Alan (Journal of Industrial Automation and Electrical Engineering, 2025)
Uncontrolled use of electrical energy in boarding houses and rentals often causes waste of power and high electrical loads. This research aims to design an Internet of Things (IoT)-based electric power monitoring and control system in two rooms using ESP32 microcontroller, PZEM-004T sensor, and OLED display. The system is integrated with the Blynk platform for remote monitoring, six relays to control electrical loads, and Google Sheet as a medium for storing monitoring data. Tests were conducted using several types of loads, including a 15-watt lamp, soldering iron, fan, cell phone charger, and 600-watt water heater. The test results showed a difference in readings between the sensor and multimeter with an average percentage error of 0.3% for voltage, 4% for current, and 0.53% for power. The current error is relatively high because the current value is so small that the difference slightly affects the percentage. In addition, testing on the relay shows that the system is able to automatically cut off the current when the cost limit is reached, as well as the buzzer works well when the cost limit is approaching. Based on these results, this system can be an effective solution in saving energy and controlling electricity usage based on IoT